Do labetalol and methyldopa have different effects on pregnancy outcome? Analysis of data from the Control of Hypertension In Pregnancy Study (CHIPS) trial. (11th August 2015) - Magee, LA; ,; von Dadelszen, P; Singer, J; Lee, T; Rey, E; Ross, S; Asztalos, E; Murphy, KE; Menzies, J; Sanchez, J; Gafni, A; et al.
Abstract : Objective: To compare pregnancy outcomes, accounting for allocated group, between methyldopa‐treated and labetalol‐treated women in the CHIPS Trial (ISRCTN 71416914) of 'less tight' versus 'tight' control of pregnancy hypertension. Design: Secondary analysis of CHIPS Trial cohort. Setting: International randomised controlled trial (94 sites, 15 countries). Population or sample: Of 987 CHIPS recruits, 481/566 (85.0%) women treated with antihypertensive therapy at randomisation. Of 981 (99.4%) women followed to delivery, 656/745 (88.1%) treated postrandomisation. Methods: Logistic regression to compare outcomes among women who took methyldopa or labetalol, adjusted for the influence of baseline factors. Main outcome measures: CHIPS primary (perinatal loss or high level neonatal care for >48 hours) and secondary (serious maternal complications) outcomes, birthweight <10th centile, severe maternal hypertension, pre‐eclampsia and delivery at <34 or <37 weeks. Results: Methyldopa and labetalol were used commonly at randomisation (243/987, 24.6% and 238/987, 24.6%, respectively) and post‐randomisation (224/981, 22.8% and 433/981, 44.1%, respectively). Following adjusted analyses, methyldopa (versus labetalol) at randomisation was associated with fewer babies with birthweight <10th centile [adjusted odds ratio (aOR) 0.48; 95% CI 0.20–0.87]. Methyldopa (versus labetalol) postrandomisation was associated with fewer CHIPS primary outcomes (aOR 0.64; 95% CI 0.40–1.00), birthweight <10th centile (aOR 0.54; 95% CI 0.32–0.92), severe hypertension (aOR 0.51; 95% CI 0.31–0.83), pre‐eclampsia (aOR 0.55; 95% CI 0.36–0.85), and delivery at <34 weeks (aOR 0.53; 95% CI 0.29–0.96) or <37 weeks (aOR 0.55; 95% CI 0.35–0.85). Conclusion: These nonrandomised comparisons are subject to residual confounding, but women treated with methyldopa (versus labetalol), particularly those with pre‐existing hypertension, may have had better outcomes. Tweetable abstract: There was no evidence that women treated with methyldopa versus labetalol had worse outcomes. Tweetable abstract: There was no evidence that women treated with methyldopa versus labetalol had worse outcomes.